Studi Potensi Interaksi Obat pada Resep Polifarmasi di Dua Apotek Kota Bandung - Irianti Bahana Maulida Reyaan; Cempaka Kuning; I Ketut Adnyana (Faculty of Pharmacy, Universitas Gadjah Mada)
Polypharmacy prescription very commonly occurs on patient’s prescription in every health facilities. Polypharmacy may increase the risk of Drug-drug Interactions (DDI’s) which mostly causes harm impact in the patient’s therapy. Drug interactions considered clinically significant if it increases the toxicity or decreases the effectiveness of therapy. The objective of this study was to analyze the potential drug interactions in polypharmacy prescriptions in two pharmacy at Bandung city in general, based on the severity, and mechanism. This study was a non-experimental study that was carried out retrospectively by taken prescription data that received by two Pharmacies in Bandung City for the period of October- December 2018. Samples were obtained by purposive sampling technique and were analyzed by using Stockley’s Drug Interaction 9th Edition and database such as micromedexsolutions.com to determine the potential for drug interactions based on its severity and mechanism of interactions. A total of 1218 prescriptions were analyzed, of which 896 prescription (73.56%) were included in the inclusion criteria, and 569 prescription (63.50%) had potential drug-drug interactions. Based on the severity, majority of drug-drug interaction is moderate (85.60%), followed by minor interactions (9.28%), and major interactions (5.12%). Based on the mechanism, majority of drug-drug interactions is pharmacodynamic interactions (90.34%), and followed by pharmacokinetic interactions (9.66%). Based on the many of potential drug interactions, polypharmacy prescribing should be avoided and management of potential DDI’s should be performed.